An Analysis Of The Preparation Of Financial Statements Based On Accounting Standards For Micro, Small And Medium Entities At Meubel Asa Pratama Panorama Of Bengkulu City - Neri Susanti; Sonalia Antama putri; Dewi Harwini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to find out whether the Meubel Asa Pratama Panorama Business had recorded financial reports in accordance with the 2018 Micro Small and Medium Entity Financial Accounting Standards. The financial accounting standards for micro, small and medium entities are standards that were made simple by the Indonesian Accounting Association in 2016 but came into effect on January 1, 2018. These standards are made in three forms of financial statements, namely statements of financial position, profit and loss and notes on financial statements that can be used by micro, small and medium enterprises. The Meubel Asa Pratama Panorama Business is engaged in the fignuture field which produces or produces various forms of wood carvings such as tables, chairs, cabinets etc. This business has been established since 1993 until now which is located at Jl. Merapi Ujung No.67 Rt.26 Rw.09 Panorama of Bengkulu City. Methods of analysis In this study using comparative descriptive method. Make a comparison between the financial statements of Asa Pratama Panorama of Bengkulu City with the 2018 Financial Accounting Standards for Micro, Small and Medium Entities financial statements which consist of statements of financial position, profit and loss and notes to financial statements. The results showed that the Meubel Asa Pratama Panorama Business in Bengkulu City had prepared or recorded an appropriate financial position report of around 61.1%, a profit and loss report of 26.6% and notes on financial statements of 0%, so a comparison between the financial statements of Asa Pratama Panorama of Bengkulu city with Financial Accounting Standards for Small and Medium Micro Entities of 2018 cannot be said to be appropriate.